Exploration of 3D stagnation-point flow induced by nanofluid through a horizontal plane surface saturated in a porous medium with generalized slip effects - Zaib, Aurang; Yangyang, Yu; Khan, Umair; Ishak, Anuar; Waini, Iskandar; Raizah, Zehba; M. Galal, Ahmed (Elsevier B.V., 2023)
Heat transfer enhancement is a contemporary challenge in a variety of fields such as electronics, heat exchangers, bio and chemical reactors, etc. Nanofluids, as innovative heat transfer fluids, have the potential to be an efficient tool for increasing energy transport. This benefit is obtained as a result of an enhancement in effective thermal conductivity and an alteration in the dynamics of fluid flow. Thus, this paper is concerned with heat transfer enhancement via nanofluids. The intention is to find numerical double solutions to the 3D stagnation-point flow (SPF) and heat transfer incorporated nanoparticles in a porous medium with generalized slip impacts. Appropriate similarity variables are used to nondimensionalize the leading equations, which are then numerically solved using the three-stage Lobatto IIIa integration formula. The impacts of different parameters on the dynamics of flow and characteristics of heat transfer induced by nanofluids in the presence of an unsteady parameter, nanoparticle volume fraction, velocity slip parameter, and porosity parameter are investigated. Based on the latest findings, it is closed that the velocity slip improves the heat transfer as well as shear stress in the axial direction in both solutions, while the shear stress behaves oppositely in the respective lateral direction. In addition, the velocity profile remarkably enriches for both branch solutions, while the temperature distribution elevates for the upper branch and declines for the lower branch owing to the larger porosity parameter.